An empirical assessment of Islamic leadership principles - Khaliq, Ahmad (Emerald Group Publishing Limited, 2011)
The main purpose of the present paper is to document some Islamic leadership principles of management. The paper equally examines the leadership function as adopted by academic administrators within the International Islamic University, Malaysia vis-a-vis Islamic principles of management. The whole process is an attempt to conduct an empirical study of the important role of excellent leadership from an Islamic perspective.